1990
DOI: 10.1111/j.1365-2133.1990.tb14724.x
|View full text |Cite
|
Sign up to set email alerts
|

Beta-adrenergic stimulation of cyclic AMP is defective in cultured dermal fibroblasts of psoriatic subjects

Abstract: Epidermal cells from psoriatic lesions demonstrate a very low cAMP response to beta-adrenergic stimuli. We have shown that a similar abnormality occurs in dermal fibroblasts from affected areas of skin. The cells, after 5-12 passages in tissue culture, had a much reduced response to 10(-8) M and 10(-6) M isoproterenol when compared with fibroblasts from control subjects. The abnormality was not abolished by the addition of the phosphodiesterase inhibitor, 3-isobutyl-I-methylxanthine. Other putative agonists te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…This could support recent observations that CyA and perhaps also FK 506 influence not only immunocom petent cells but also kératinocytes in the treat ment of this disease. Our results agree with those investigators postulating that the induc tion of cAMP is probably a positive mitogenic and morphogenic signal required for the in duction of cell growth and differentiation [28,31,34,35,37]. Since immunosuppressive drugs reduced the cAMP level in psoriatic kératinocytes, it is very doubtful that low lev els of cAMP should be a trigger for the epider mal hyperproliferation in psoriasis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This could support recent observations that CyA and perhaps also FK 506 influence not only immunocom petent cells but also kératinocytes in the treat ment of this disease. Our results agree with those investigators postulating that the induc tion of cAMP is probably a positive mitogenic and morphogenic signal required for the in duction of cell growth and differentiation [28,31,34,35,37]. Since immunosuppressive drugs reduced the cAMP level in psoriatic kératinocytes, it is very doubtful that low lev els of cAMP should be a trigger for the epider mal hyperproliferation in psoriasis.…”
Section: Discussionsupporting
confidence: 78%
“…How ever, in contrast to the findings of Eedy et al [28], we did not detect differences in the cAMP stimulation of kératinocytes derived from psoriatics compared with those derived from controls. In contrast to an old opinion that only physiological or low levels of cAMP are positive regulators of cell growth and dif ferentiation and could be responsible for hy perproliferation of kératinocytes as seen in psoriasis [12,29,30], recent investigations indicate that elevated cAMP levels initiate the proliferation of a number of eukaryotic cells, e. g. kératinocytes and lymphocytes [17,[31][32][33][34][35], An increase in cAMP has been shown to induce the transcription of different genes, involving the activation of the cAMP-response-element-binding protein and the c-fos and c-myc mRNA expression [33,35], Fur thermore, it could be demonstrated that the 11-2 and IFN-y production was enhanced after activating the catalytic subunit Ca of the pro tein kinase A [36], Therefore, inhibition of cAMP formation followed by a decrease in protein kinase A activity may decrease lym phokine synthesis and secretion.…”
Section: Discussioncontrasting
confidence: 57%
“…In atopic eczema there is a point mutation in the ␤2-AR gene and a low ␤2-AR density on keratinocytes and peripheral blood lymphocytes (Schallreuter, 1997). In psoriasis, epidermal cells from psoriatic lesions demonstrate a low cAMP response to ␤2-AR activation (Eedy et al, 1990). Additionally, a paracrine role for the hormone mediator network in skin homeostasis has been demonstrated recently as keratinocyte catecholamine synthesis can regulate melanogenesis in melanocytes (Gillbro et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes derived from patients with atopic eczema display a point mutation in the ␤2-AR gene and a low ␤2-AR density (7). In psoriasis, keratinocytes within the psoriatic lesions demonstrate a low cAMP response to ␤2-AR activation (8). These findings point to a role for the ␤2-AR in maintaining epidermal function and integrity.…”
Section: ␤-Adrenergic Receptors (␤-Ars)mentioning
confidence: 83%